Impaired sense of smell and altered olfactory system in RAG-1−∕− immunodeficient mice - Rattazzi, Lorenza; Cariboni, Anna; Poojara, Ridhika; Shoenfeld, Yehuda; D'acquisto, Fulvio (Frontiers in Neuroscience, 2015)
Immune deficiencies are often associated with a number of physical manifestations including loss of sense of smell and an increased level of anxiety. We have previously shown that T and B cell-deficient recombinase activating gene (RAG-1)-/- knockout mice have an increased level of anxiety-like behavior and altered gene expression involved in olfaction. In this study, we expanded these findings by testing the structure and functional development of the olfactory system in RAG-1-/- mice. Our results show that these mice have a reduced engagement in different types of odors and this phenotype is associated with disorganized architecture of glomerular tissue and atrophy of the main olfactory epithelium. Most intriguingly this defect manifests specifically in adult age and is not due to impairment in the patterning of the olfactory neuron staining at the embryo stage. Together these findings provide a formerly unreported biological evidence for an altered function of the olfactory system in RAG-1-/- mice.